Integration of Islam and Science in Interdisciplinary Islamic Studies - Hasan Abidin (Institut Agama Islam At-Tahdzib, 2025)
Science plays a crucial role in Islam. No other religion, and no holy book like the al-Qur’an, places such a high value on knowledge and commands its adherents to seek it. Islam is a religion of salvation that does not separate knowledge into dichotomous boxes. Islam should not be separated from science; instead, it should be integrated. Everything in the universe, including human creation and culture, essentially belongs to and originates from Allah. Science and technology are developing rapidly. Allah has provided humans with the tools of reason and senses to produce knowledge, as well as the universe and its contents. All of this serves the purpose of science and technology, which are based on religion. Science, as it develops, can originate from religious, rational, empirical sources, or a combination of all three. The integration of Islamic religious knowledge with science, or vice versa, implies that all knowledge ultimately originates from Allah. All manifestations of knowledge are ultimately aimed at serving God Almighty.